Impact of Android-Based Reproductive Health Education on Knowledge Improvement Among Adolescent Girls in Takalar, Indonesia: A Quasi-Experimental Study in a Senior High School - Sumarmi Sumarmi; Wahyuni Hidayati; Ernawati Ernawati; Salmah Arafah; Alwi Alwi; Raufina Riandhani Mulyoto (STIKep PPNI Jawa Barat, 2026)
Background: Adolescent girls are particularly vulnerable to reproductive health problems due to limited knowledge and inadequate access to reliable information. Innovative educational strategies are needed to improve their understanding of reproductive health. Objective: This study aimed to evaluate the effectiveness of Android-based reproductive health education in improving knowledge among adolescent girls. Methods: A quasi-experimental study with a pretest–posttest control group design was conducted among 100 female students at a senior high school in Takalar, Indonesia. Participants were divided into an intervention group (n = 50) and a control group (n = 50). The intervention group received reproductive health education through an Android-based application, while the control group continued routine school activities. Knowledge was assessed using a structured questionnaire administered before and after the intervention. Data were analyzed using descriptive statistics and the Mann–Whitney U test. Results: The intervention group showed a substantial increase in mean knowledge scores from pre-test to post-test (11.52 ± 3.04 to 17.54 ± 2.29), while the control group demonstrated only a slight change (12.86 ± 3.74 to 13.24 ± 4.22), indicating greater short-term knowledge improvement in the intervention group. Conclusion: Android-based reproductive health education effectively improves knowledge among adolescent girls and represents a promising digital approach for school-based health promotion